The Influence of Green Products and Green Prices on Customer Satisfaction with Cleo Brand Bottled Drinking Water Products through Purchasing Decisions as an Intervening Variable - Riz Jannah Yahya; Supriyono Supriyono; Mira Meilia Marka (The Graduate School of Sahid University, 2023)
This study aims to analyze the effect of green product and green price on customer satisfaction in bottled water product (AMDK) brand Cleo through purchasing decisions as intervening variable (a case study on residents of Mejobo District, Kudus Regency). The population of this study were consumers of Cleo brand bottled drinking water (AMDK) among residents of Mejobo District, Kudus Regency, the sample used in this research was 100 respondents using primary and secondary data. The sampling technique used purposive sampling with a structural equation model data analysis method using the AMOS program. The research of the results that green products have no effect on purchasing decisions. Green price has a positive and significant effect on purchasing decisions. Green products have no effect on customer satisfaction. Green price has no effect on customer satisfaction. Purchasing decisions have a positive and significant effect on customer satisfaction. Purchasing decisions cannot mediate green products on customer satisfaction. Purchasing decisions cannot mediate green prices on customer satisfaction.